(untitled) (CIPEEX, 2022)
CURRENTLY, WITH THE ADVENT OF TECHNOLOGY, MORE AND MORE MODERN TECHNOLOGIES ARE AVAILABLE ANDINNOVATIVE SOLUTIONS, WHETHER THROUGH SMARTPHONES, TABLETS OR COMPUTERS, AND THESE ARE USED TO FACILITATEOUR DAY TO DAY, BOTH IN THE CITY AND IN THE COUNTRYSIDE. MAKE GOOD USE OF THE TECHNOLOGICAL RESOURCES THAT AREAVAILABLE, CAN MAKE PROFESSIONALS, MAINLY IN AGRIBUSINESS, INCREASE THEIRPRODUCTION EFFICIENCY, SAVE TIME AND GET THE BEST POSSIBLE FINANCIAL RETURN. IN THIS BIAS, IT IS NECESSARYPOINT OUT THAT, THROUGH AGRO SAFARI, IT WILL BE POSSIBLE TO CARRY OUT MORE EASILY AND PRACTICALLY THEMANAGEMENT OF THE MAIN AGRIBUSINESS PROCESSES THROUGH THE RESOURCES MADE AVAILABLE WITHIN THEPLATFORM. THUS, IN ORDER TO PROMOTE GREATER INTERACTION BETWEEN TECHNOLOGY AND AGRIBUSINESS, THE DISCIPLINEOF INTERDISCIPLINARY PRACTICE: PROCESS MANAGEMENT CONTRIBUTED TO THE PROBLEMATIZATION AND MANAGEMENT OF THEPROJECT, THE PROGRAMMING LABORATORY DISCIPLINE CONTRIBUTED TO THE DEVELOPMENT AND IMPROVEMENT OF THEPLATFORM AND FINALLY THE DISCIPLINE OF ANALYSIS AND SOFTWARE DESIGN HELPED IN THE GATHERING OF REQUIREMENTS ANDSCREEN PROTOTYPING.